Weevil resistant sweetpotato through biotechnology - International Potato Center (2016)
Weevils damage about a quarter of the sweetpotato harvest in Uganda and induce the accumulation of toxic compounds in the healthy-looking parts of damaged storage roots. We have introduced new genes that produce new proteins and small RNA against weevils in the sweetpotato storage root through biotechnology. We may have found few plants with some resistance to weevils. In parallel, we continue producing more plants with small RNA to weaken specific genes of the weevils to block their development. These two strategies may eventually be combined into widely-cultivated sweetpotato varieties in SSA.